An Office Procedure Development of Library Department in Bestlink College of the Philippines at Novaliches, Quezon City: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Library Department of Bestlink College of the Philippines must improve its traditional and online procedures. To address this, researchers proposed a plan to enhance their workflow. The goal of this study is to recommend solutions to the challenges faced by the department and emphasize the importance of well-maintained and organized office procedures. The library's achievement does not necessarily determine how good its procedures are, as unforeseen situations can arise and test its ability to provide quality service to students. To conduct this study, researchers used a Qualitative Method and Descriptive Research Design, interviewing five staff and personnel, including the Library Director. Based on their findings, the researchers proposed updating equipment and technologies to support online services, implementing a learning continuity plan/disaster action plan, and establishing a procedure for distance learning by borrowing library materials online. These solutions will improve the effectiveness of the library and prevent difficulties that may arise in the future. It is also advised that the BCP Library works with other departments to accomplish common goals and that the department be highlighted on the BCP webpage to attract students.
Keywords: Library; Librarian; Office Procedure; Development